Alcohol and prescribed psychotropic drug use among patients admitted to a department of old-age psychiatry in Norway. Issue 1 (February 2017) - Johannesen, Aud; Engedal, Knut; Larsen, Marianne; Lillehovde, Elin; Stelander, Line Tegner; Helvik, Anne-Sofie
Background: Although alcohol and prescribed psychotropic drug use has increased among older people, the usefulness of information provided about these substances in patients' referrals to departments of old-age psychiatry (OAPsy) is unknown. Aims: To examine whether patients' self-reported elevated use of alcohol and prescribed psychotropic drugs corresponds with information provided in the referrals to OAPsy departments and to explore the factors associated with elevated self-reported use of these substances. Methods: We recorded the information provided in referrals about the elevated use of alcohol and psychotropic drugs in a sample of 206 patients (69 men) from 12 OAPsy departments. The Alcohol Use Disorders Identification Test (AUDIT) and Drug Use Disorders Identification Test (DUDIT) helped to assess self-reported use. We also collected demographic data, as well as information about cognitive functioning and symptoms of anxiety and depression. Results: Seventy-three patients (35%) scored above the cut-off for alcohol use for women/men (AUDIT ≥ 3/4) or psychotropic drugs (DUDIT ≥ 6/8), if not both. Twenty patients (10%) reported an elevated use of both alcohol and psychotropic drugs, and the referrals for eight (40%) and ten (50%) of them, respectively, included information about this use. There was a significant association between self-reported use of alcohol above the cut-off and information about elevated use in the referrals. However, no such association was found between information in the referrals and self-reported use of prescribed psychotropic drugs. Elevated alcohol use was associated with more years of education, while elevated use of psychotropic drugs was associated with younger age and severe symptoms of anxiety and depression. Conclusion: The information reported in referrals about the elevated use of alcohol and psychotropic drugs demonstrated a trend in associations with self-reported use. However, the risk factors for elevated use of alcohol and psychotropic drugs in the elderly need to be examined further.